Diseño de un modelo de integración de los actuantes de una red de valor de ciclo cerrado para la industria manufacturera de Bogotá, basado en herramientas de inteligencia emocional y estilos de liderazgo (2020)
Through this research project it is intended to find the solution to the identified problem, such as the lack of integration of the operators of the closed loop supply chain, which, through the design of an integration model, based on the tools of psychological profiles, the pillars of emotional intelligence and leadership styles, aims to mitigate the causes and the most incident factors, which according to this problem, cause the actuators of the closed loop supply chain, do not achieve proper alignment and integration, which causes this to have a negative influence on the operation of the supply chain.